Integrasi kegiatan laboratorium dan kontribusi terhadap hasil belajar fisika pada konsep fluida dalam pembelajaran fisika SMA - Sharmila Sharmila; Amali Putra (PILLAR OF PHYSICS EDUCATION, 2019)
Laboratory activities are  must implemented in high school physics learning so that learning is carried out contextually based on observation. The problems faced in high school physics learning are not yet optimal laboratory activities carried out so that the level of understanding of students is low which has an impact on learning outcomes that have not been satisfactory. This study aims to determine the effect of integration of laboratory activities on the achievement of high school physics learning outcomes in class XI SMA Adabiah Padang. The study was conducted in the July-December 2018 semester for fluid concepts in the form of quasy experimental with design  post-test control only group design. The research data is in the form of understanding physics concepts that are captured using LKPD and post test. The instrument used has been tested beforehand. The results showed that the average value of the experimental class was 70.85 higher than the control class value of 63.2. The results of the t test at a significant level of 0.05 indicate that th = 2.53 while tt = 2.46. Differences in learning outcomes due to differences in treatment. Furthermore, from the regression analysis, the correlation between LKPD scores and post test obtained rxy = 0.563, meaning that in this study there were 31%. This study concludes that there is a significant effect of the application of laboratory activities to student learning outcomes